2019
DOI: 10.15583/jpchrom.2019.009
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Behaviors of In-Source Collision Induced Dissociation and Shifting the Linear Range of Calibration Curves of Various Drugs and the Metabolites Used for Therapeutic Drug Monitoring

Abstract: Therapeutic drug monitoring (TDM) is a clinical practice that designs personalized medication for patients with blood concentrations of the drug. TDM approach is used for many drugs, including immunosuppressant, antifungal, antiarrhythmic, and anti-cancer drugs. Combination therapies are often adopted in TDM. Liquid chromatography tandem mass spectrometry (LC-MS/MS) is a useful analytical method in such cases. However, the development of a simultaneous LC-MS/MS analytical method is difficult owing to the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The LC–MS/MS conditions were set as previously described (Maekawa et al, 2019. An LCMS‐8050 triple quadrupole mass spectrometer (Shimadzu, Kyoto, Japan) coupled with a Nexera ultra high‐performance liquid chromatograph system (Shimadzu) was used as the LC–MS/MS system.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The LC–MS/MS conditions were set as previously described (Maekawa et al, 2019. An LCMS‐8050 triple quadrupole mass spectrometer (Shimadzu, Kyoto, Japan) coupled with a Nexera ultra high‐performance liquid chromatograph system (Shimadzu) was used as the LC–MS/MS system.…”
Section: Methodsmentioning
confidence: 99%
“…The MS conditions were set as follows: probe voltage, 4000 V; interface temperature, 300 C; desolvation line temperature, 250 C; block heater temperature, 400 C; nebulizing gas flow, 3 L/min; drying gas flow, 10 L/min; and heating gas flow, 10 L/min. The selected reaction monitoring conditions for each analyte were optimized as previously described (Table 1, Maekawa et al, 2019).…”
Section: Lc-ms/ms Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Maekawa et al reported on in-source collision-induced dissociation and shifting the linear range of calibration curves for therapeutic drug monitoring using UHPLC-MS/MS. 5 Multi-dimensional HPLC is highly effective for the analysis of trace analytes (such as amino acids) in complicated biological samples, as reported by Hamase et al 6 Additionally, HPLC has found applications in other analytical fields, such as analyses of environmental samples 7-10 and foods. [11][12][13][14] The development of new stationary phases is essential to achieve varied and desirable selectivity in HPLC.…”
mentioning
confidence: 92%